Recensions / Book Reviews: Paris Arnopoulos, Mediterranean 2000 - Constantinides, Stephanos (Études helléniques / Hellenic Studies, 1995)
PARIS ARNOPOULOS, MEDITERRANEAN 2000, VOLUME 1 , ATHENS, FOUNDATION FOR MEDITERRANEAN STUDIES, 1992, P. 206